2021
DOI: 10.18502/jovr.v16i1.8256
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of COVID-19: A Systematic Review and Meta-analysis

Abstract: Several studies have reported the characteristics of Coronavirus disease 2019 (COVID-19), yet there is a gap in our understanding of the ocular manifestations of COVID-19. In this systematic review and meta-analysis, we investigated the prevalence of ocular manifestations in COVID-19 patients. We searched Pubmed, Embase, Scopus, Web of Science, and medRxiv from December 1, 2019 to August 11, 2020. Two independent reviewers screened the articles, abstracted the data, and assessed the quality of included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 61 publications
2
129
2
5
Order By: Relevance
“…On the other hand, we also have to consider that dry eye, together with the sensation of a foreign body, redness, tearing, itching, eye pain, and discharge were the most important ocular manifestations in patients with COVID-19. In the systemic review by Nasiri et al [ 55 ], it was concluded that the mechanism of dry eye or foreign body sensation is unclear in COVID-19 patients and may not be directly associated with SARS-CoV-2. The appearance of dry eye during the COVID-19 epidemic can be related to the use of face masks, mainly when the masks are loose against the face and nose, and the airflow is greater towards the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we also have to consider that dry eye, together with the sensation of a foreign body, redness, tearing, itching, eye pain, and discharge were the most important ocular manifestations in patients with COVID-19. In the systemic review by Nasiri et al [ 55 ], it was concluded that the mechanism of dry eye or foreign body sensation is unclear in COVID-19 patients and may not be directly associated with SARS-CoV-2. The appearance of dry eye during the COVID-19 epidemic can be related to the use of face masks, mainly when the masks are loose against the face and nose, and the airflow is greater towards the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes a vast number of studies and articles indicating that DED is likely to have been worsened during the COVID-19 pandemic period [32][33][34][35][36]. In addition to the ocular signs and symptoms reported among people contracting the COVID-19 virus, the lifestyle changes associated with social distancing measures and the wearing of masks have implications for ocular health [32][33][34][35][36][37][38][39]. The term ''quarantine dry eye'' has been proposed by Napoli et al in their recent hypothesis paper discussing the aspects of lockdown lifestyle likely to affect ocular surface health, from environmental and behavioural factors through to diet, hydration, sleep deprivation and the psychological challenges associated with the pandemic restrictions [32].…”
Section: Evolution Of Dry Eye Disease During the Covid-19 Pandemicmentioning
confidence: 99%
“…Among the patients with COVID-19 in the acute phase of the disease, approximately 10% exhibited ocular symptoms, particularly related to ocular surface (conjunctivitis, red eye, foreign body sensation, dry eye, photophobia, blurry vision, itching, epiphora, ocular pain, and floaters) 3 6 . Concerning posterior segment commitment, flame-shaped or microhemorrhages and cotton wool spots in the papillomacular bundle were shown 7 9 .…”
Section: Introductionmentioning
confidence: 99%